Knowledge and practice of routine medical check-up Among elderly in Klinik Rawatan Keluarga (KRK), Hospital Universiti Sains Malaysia (HUSM) - Wahab, Patimah Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2007)
Objective To examine elderlys' knowledge, health practice and attitude toward routine medical check-up. Design and setting A cross-sectional descriptive study was conducted at Klinik Rawatan Keluarga (KRK), Hospital Universiti Sains Malaysia (HUSM). Methods A convenience sample of 90 men and women aged 60 years and above, completed answering questionnaires of sociodemographic data, knowledge of routine medical check-up, practice and attitude. Findings Educational level and socioeconomic factor (income) influenced elderlys' knowledge and attitude. Meanwhile, health status influenced elderly practice. Conclusions The study revealed that one's knowledge does not necessarily reflect one's actual practice status. This finding deserves the attention of older adult and health care providers who consider patient awareness as fundamental to behavioral changes and health centre visits for regular medical check-up.